2010
DOI: 10.1088/0957-4484/21/30/305706
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the use of magnetic force microscopy to discriminate between magnetic and nonmagnetic nanoparticles

Abstract: Magnetic force microscopy (MFM) is a very powerful technique, which can potentially be used to detect and localize the magnetic fields arising from nanoscopic magnetic domains, such as magnetic nanoparticles. However, in order to achieve this, we must be able to use MFM to discriminate between magnetic forces arising from the magnetic nanoparticles and nonmagnetic forces from other particles and sample features. Unfortunately, MFM can show a significant response even for nonmagnetic nanoparticles, giving rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 26 publications
10
68
0
Order By: Relevance
“…All the measurements were conducted in air and at room conditions without applying an external magnetic field. We would explicitly note that while some authors pointed out the importance of the presence of an external field 29 , 88 when performing MFM images of MNPs, other authors successfully performed MFM experiments without the external field, the magnetization of the MNPs being obtained as the result of the magnetic field produced by the MFM tip 30 , 70 , 89 , 90 . In this work, in order to verify if the localized magnetic field produced by our tips were capable of magnetizing the MNPs preliminary tests have been performed using a permanent magnet under the sample.…”
Section: Methodsmentioning
confidence: 99%
“…All the measurements were conducted in air and at room conditions without applying an external magnetic field. We would explicitly note that while some authors pointed out the importance of the presence of an external field 29 , 88 when performing MFM images of MNPs, other authors successfully performed MFM experiments without the external field, the magnetization of the MNPs being obtained as the result of the magnetic field produced by the MFM tip 30 , 70 , 89 , 90 . In this work, in order to verify if the localized magnetic field produced by our tips were capable of magnetizing the MNPs preliminary tests have been performed using a permanent magnet under the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Similar findings relating to other non-magnetic materials have previously been commented upon in MFM studies reported by other groups. 38,64,65 Upon increasing the lift height to >10 nm however, this positive contrast associated with the uncoated DNA regions was rapidly lost, whilst the negative contrast correlating with the Fe 3 O 4 -coated DNA regions remained clearly evident. The persistence of this negative contrast at increased lift heights confirms these features arise as a consequence of long-range magnetic interactions between the probe and sample, substantiating the room-temperature magnetic behaviour of the Fe 3 O 4 when prepared in such a nanostructured form.…”
Section: Magnetic Force Microscopymentioning
confidence: 99%
“…However, MFM is nowadays proposed as a valuable technique to characterize more complex systems such as organic nanomagnets [6], magnetic oxide films [7], superparamagnetic particles [89] and carbon based materials [1011]. In general, these materials present low magnetic moment at room temperature.…”
Section: Introductionmentioning
confidence: 99%